ChemInform Abstract: Harnessing the Electrophilicity of Keteniminium Ions: A Simple and Straightforward Entry to Tetrahydropyridines and Piperidines from Ynamides. Issue 31 (14th July 2016) - Lecomte, Morgan; Evano, Gwilherm
Abstract: The title compounds are prepared by a formal intramolecular hydroalkylation of readily available substituted ynamides which generate highly reactive activated keteniminium ions upon simple activation under acidic conditions.